Validity and Reliability of Index of Learning Styles for Vocational Students Using the Rasch Measurement Model - Suhaini, Mazlili; Ahmad, Adnan; Mohd Bohari, Normila; Mohammad, Norliza (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this paper is to generate empirical evidence on the validity and reliability of modified items in the Index of Learning Styles instrument by applying the Electrical Technology vocational elements. The instrument has been distributed to a sample of 60 Electrical Technology students at a vocational college. The Rasch measurement model was used to examine the functional items and detect the item and respondent reliability and index separation, the polarity of the item, measuring the fit of the item in measuring the construct, and standardized residual correlation values. The final findings showed that only four items did not meet the criteria, and 31 items remained suitable to measure the four constructs. There were two implications. First, this analysis helped the educators to investigate their students learning styles in order to select a suitable teaching strategy or approach that focused on the students’ learning style. Second, the data obtained will develop a vocational learning style framework that could assist the BPTV and curriculum planning division in designing and organizing activities in line with the students’ learning styles. This study is the first effort to establish valid constructs for the development of an instrument for assessing vocational learning styles.